2011
DOI: 10.1186/1758-2652-14-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition outcomes of HIV‐infected malnourished adults treated with ready‐to‐use therapeutic food in sub‐Saharan Africa: a longitudinal study

Abstract: BackgroundAmong people living with HIV/AIDS, nutritional support is increasingly recognized as a critical part of the essential package of care, especially for patients in sub-Saharan Africa. The objectives of the study were to evaluate the outcomes of HIV-positive malnourished adults treated with ready-to-use therapeutic food and to identify factors associated with nutrition programme failure.MethodsWe present results from a retrospective cohort analysis of patients aged 15 years or older with a body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(121 citation statements)
references
References 21 publications
9
104
7
Order By: Relevance
“…Perceptions and experiences of PLHIV and HSA living in different regions of Malawi may differ. However, the study findings are consistent across different sources of information (PLHIV and HSA), sex (male and female) and are consistent with findings of studies from other African countries (14,17,18) . Participants' responses to some topics, particularly the positive influence of eating behaviours attributed to counselling sessions imparted by HSA, and food habits, might have been biased, due to a social desirability, especially because the IDI were conducted at the Chilomoni clinic.…”
Section: Limitations and Strengthssupporting
confidence: 89%
See 1 more Smart Citation
“…Perceptions and experiences of PLHIV and HSA living in different regions of Malawi may differ. However, the study findings are consistent across different sources of information (PLHIV and HSA), sex (male and female) and are consistent with findings of studies from other African countries (14,17,18) . Participants' responses to some topics, particularly the positive influence of eating behaviours attributed to counselling sessions imparted by HSA, and food habits, might have been biased, due to a social desirability, especially because the IDI were conducted at the Chilomoni clinic.…”
Section: Limitations and Strengthssupporting
confidence: 89%
“…RUTF shows promising results in achieving a more prompt restoration of BMI (14,27) and fatfree mass (27) , and is increasingly being used in nutrition supplementation programmes (18) . However, increasing evidence shows that the acceptance of RUTF is low among adult PLHIV (14,17) .…”
Section: Discussionmentioning
confidence: 99%
“…24e26 The importance of ready-to-use therapeutic food (RUTF) in malnourished HIV-infected patients has been established. 27 In a similar fashion, malnourished TB patients are likely to benefit from RUTF. However, further studies are required to confirm the role of RUFT in malnourished TB patients.…”
Section: Discussionmentioning
confidence: 95%
“…Ready-to-use therapeutic foods effectively treat malnutrition of HIV-infected individuals in developing nations [18]. In a study of 1340 HIV-infected adults in sub Saharan Africa with body mass indices of less than 17 kg/m 2 , ready-to-use therapeutic food (2000 kilocalories per day) increased the chances of nutritional recovery in severely malnourished HIV-infected patients [18]. However, this retrospective analysis also showed that 48% of patients failed therapy because of lost-to-follow-up, poor adherence to ART, or severe malnutrition at baseline.…”
Section: Nutritional Interventionsmentioning
confidence: 99%